Total Ozone over Vernadsky Antarctic Station: Ground-based and Satellite Measurements - Grytsai, A. V.; Milinevsky, G. P.; Ivaniga, O. I. (Ukrainian Antarctic Journal, 2018)
Objective. Provide an analysis of the total ozone variations over Vernadsky Antarctic station (Faraday Base until 1996) from long-term ground-based and satellite series. Study the discrepancies between the data of different instruments. Methods. Data visualization followed by analysis, statistical treatment of the Vernadsky Dobson spectrophotometer observations and satellite total ozone series. Results. Satellite and ground-based measurements of total ozone over Vernadsky station have confirmed the stabilization in the ozone layer in the stratosphere over Antarctica from the early 2000s. British Faraday Base observations have retrieved an ozone spring maximum during the 1950s–1970s with a sharp decrease in the August–October values in the 1980s–1990s. That changed substantially total ozone seasonal cycle. Satellite overpasses and model data based on satellite measurements have been analyzed. It is shown that typical discrepancies between the Ozone Monitoring Instrument (OMI) model and the Vernadsky Dobson daily means are mainly in the range of 20 DU. Larger deviations are rare and are observed predominantly on the beginning and at the end of the observational season. Seasonal means and standard deviations for the model–Dobson differences were calculated that demonstrates worse correspondence of the OMI model with Vernadsky Dobson data during separate years, in particular 2009–2010. Conclusions. Both Dobson and satellite ozone data over Faraday/Vernadsky station have shown the total ozone decrease during the 1980s–1990s (mainly in spring) with a following stabilization since year 2000. Comparison between the ground-based data and models calculated from satellite measurements indicates better correspondence of the Dobson and GOME2 results relatively the OMI ones. There are evidences that individual Dobson measurements underestimate to some degree total ozone on the beginning of observational season at high solar zenith angles and the low total ozone values.